THE USE OF BOTULINUM TOXIN IN THE TREATMENT OF FACIAL PARALYSIS (Editora Impacto Científico, 2025)
Peripheral facial paralysis, or Bell's palsy, is a condition that affects the facial muscles on one side of the face, causing uneven facial expressions. It can have several causes, such as viral infections, syndromes, or traumatic injuries. One form of treatment is the use of botulinum toxin type A, which acts by reducing muscle hyperactivity and improving facial symmetry. The objective of this study was to review the literature on the subject, using academic articles published between 2007 and 2023. The results showed that peripheral facial paralysis is a common syndrome, affecting about 70% of cases of facial paralysis. The condition is equally distributed between the sexes, and the average age at which it usually manifests is around 40 years, although it can occur at any age. Among the various serotypes of botulinum toxin, type A is the most widely used in aesthetics because it is more potent and specific. Other approaches, such as physical therapy, speech therapy, and support threads, can also aid in patient rehabilitation. Therefore, it is concluded that the use of botulinum toxin type A is a complementary alternative for the well-being of individuals affected by peripheral facial paralysis.